Avaliação da atividade antimicrobiana do cinamaldeído em isolados nosocomiais de Acinetobacter baumannii resistentes a carbapenêmicos - Morais, Ana Jessyca Alves (2018)
The emergence of A. baumannii multidrug-resistant (MDRAB) has become a worldwide critical clinical problem due to the limitation of therapeutic options for the treatment of MDRAB infections. The growing interest in new therapies based on natural products is the basic and primary source for the emergence of new antimicrobials. Therefore, the aim of this study was to evaluate the antimicrobial activity of cinnamaldehyde against 47 nosocomial strains of A. baumannii resistant to carbapenems isolated from patients in four teaching hospitals in the State of Ceará, Brasil. Phenotypic identification and susceptibility to antimicrobials were determined by the VITEK®2, additionally polymerase chain reaction (PCR) to amplify the blaOXA-51 gene was performed on all presumptively identified as A. baumannii and the clinical characteristics were analyzed. The minimum inhibitory concentration (MIC) of cinnamaldehyde was determined by the broth microdilution method according to the Clinical and Laboratory Standards Institute recommendations, and the minimum bactericidal concentration (MBC) was considered the lowest concentration of cinnamaldehyde which prevented growth and reduced the inoculum by in more than 99.9% within 24 h after incubation at 37ºC. The results showed that the MIC of the cinnamaldehyde against 47 A. baumannii nosocomial isolates ranged from 125 to 500 μg/mL (Mean = 210.93 ± 58.55) and the MBC ranged from 250 to 1000 μg / mL (Mean = 510.41 ± 230.39). It was observed that bloodstream was the most frequent isolation site, and most of the strains were isolated from Intensive Care Units. Therefore, these data demonstrated a potent inhibitory and bactericidal effect of cinnamaldehyde against carbapenem-resistant A.baumannii nosocomial strains, suggesting the prospection of this compound for the development of a new antibacterial substance, either as a medicament or in new products destined to the final disinfection of hospital environments.